بناء معجم حاسوبي تفاعلي لجذور اللغة العربية (من حرف الحاء إلى الزاي) - قماطي، أنس عبد الفتاح عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research aims to explain the lexicon gaps in traditional Arabic dictionaries and the problems caused by its methodology and to find a solution to fill these gaps. It then deals with research and tracking the stages of development of the lexicon industry until the modern renaissance of the Arabic Language by characterising the stages of the modern era of creativity and development. The study deals with how to take advantage of the technical development in the modern era, to introduce a theoretical vision to build an interactive computer dictionary and to explain the foundations of this vision. All of these processes were conducted through the use of an inductive analytical method of analysing dictionaries, articles and scientific research related to the subject, with specific focus on the lexicon. The results of this study include identifying that the Arabic lexicographic heritage is a repository for classical Arabic language, which may be used in terms of words and the Arab lexicon in general. The dictionary of standards in particular is a deep understanding of the assets and branches of the Arabic language, which linguistic technicians and dictionaries have benefitted from over successive periods. The study also concludes that the abbreviation of the meanings in the lexicon and the neglect to the mention linguistic evidence were not obstacles in the time the lexicon was made. Thus, the people who speak the Arabic language understand the concepts of the language and Islamic religion. It is expected that this research will help to reduce the gaps in Arabic dictionaries, contribute to the introduction of renewed vision and benefit from the technological globalisation in the renaissance of the Arabic language.